2019
DOI: 10.1002/lt.25411
|View full text |Cite
|
Sign up to set email alerts
|

Not All Cellular Rejections Are the Same: Differences in Early and Late Hepatic Allograft Rejection

Abstract: T cell-mediated rejection (TCMR) is common after liver transplantation (LT), and it is often thought to have a minimum impact on outcomes. Because alloimmune response changes over time, we investigated the role of the timing of TCMR on patient and allograft survival and examined the risk factors for early and late TCMR. We reviewed protocol liver biopsies for 787 consecutive LT recipients with an 8.6-year follow-up. The incidence of early TCMR (≤6 weeks after LT) was 33.5% with nonalcoholic steatohepatitis pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 31 publications
3
48
2
7
Order By: Relevance
“…Earlier data from 3 North American centers that performed surveillance biopsies demonstrated that the incidence of liver TCMR was 66% within the first year . With standardized tacrolimus‐based immunosuppression, this incidence appears to have been reduced to approximately 37.1% in the more recent era . The vast majority of the TCMR occurs within the first 6 weeks.…”
Section: Mechanisms and Types Of Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier data from 3 North American centers that performed surveillance biopsies demonstrated that the incidence of liver TCMR was 66% within the first year . With standardized tacrolimus‐based immunosuppression, this incidence appears to have been reduced to approximately 37.1% in the more recent era . The vast majority of the TCMR occurs within the first 6 weeks.…”
Section: Mechanisms and Types Of Rejectionmentioning
confidence: 99%
“…(6) With standardized tacrolimus-based immunosuppression, this incidence appears to have been reduced to approximately 37.1% in the more recent era. (7) The vast majority of the TCMR occurs within the first 6 weeks. Although mild elevation in liver enzymes typically accompanies TCMR, the sensitivity and specificity of abnormal tests are relatively low.…”
Section: Mechanisms and Types Of Rejectionmentioning
confidence: 99%
“…As previously observed, in LT, late L‐TCMR was often associated with lower immunosuppression levels, including non‐adherence 7,8 . L‐TCMR was more refractory to immunosuppressive therapy, and the evolution of L‐TCMR might result in chronic rejection or zone 3 fibrosis 9‐11 .…”
Section: Introductionmentioning
confidence: 61%
“…Late TCMR was defined as TCMR characterized by central veins or perivenular inflammation and an onset later than 3 months after LT in accordance with the Banff criteria and past literature (Figure 1). 8,10,15 Although either 3 months or 6 months can be used to define L‐TCMR due to the lack of a clear criterion for time‐to‐onset of L‐TCMR, 9 we adopted 3 months because steroid administration is stopped 3 months after the LT in accordance with our immunosuppression protocol described below. The L‐TCMR grades ranged from minimal or indeterminate to severe in accordance with the previously proposed criteria 10 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation